Plano de gerenciamento de tecnologias: conhecendo a implantação em unidades de terapia intensiva de Goiânia, Goiás - Silva, Frederico Inácio e (2019)
Although almost 10 years have passed since the publication of RDC Nº 2/2010 ANVISA that establishes the obligation of technology management in health facilities, its implementation in practice is still a challenge and a public health problem. Especially in highly specialized and technology-dependent healthcare facilities such as Intensive Care Units (ICU). This study then aimed to verify the implementation of the Technology Management Plan for Medical Equipment in the ICU of Goiânia, Goiás, an integral part of technology management. As a basis, we used secondary data collected in a Guide prepared by the Sanitary Surveillance of the municipality studied. This guide was applied twice during each visit to the municipality's ICU during tax audits. These data were analyzed comparatively in both visits and the results presented by absolute, relative frequency and statistical analysis. The PGT implementation levels found were 25.82% and 40.86% in the first and second audit, respectively. When analyzing the results individualized by type of management, it appears that the private sector, which corresponds to the vast majority of health services with ICU, had the lowest rates of implementation of PGT, while the group of health services managed by Social Organizations presented the highest rates, according to the study criteria. Regulatory and control mechanisms capable of restricting resources and disabling services such as the management contract established between the Social Organizations and the State are effective to provide improvements in the implementation of technology management. Investments in training and continuing education programs can be a direction for improving the implementation of PGT and consequently an advance in the quality of service offered to the user. Considering that Health Surveillance is an important catalyst for this change, this study provides important data for managers to prioritize actions and formulate public policies in Collective Health. Considering that Health Surveillance is an important catalyst for this change, this study provides important data for managers to prioritize actions and formulate public policies in Collective Health.